2013
DOI: 10.1371/journal.pone.0072875
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Bmy1 Alleles Increasing β-Amylase Activity in Chinese Landraces and Tibetan Wild Barley for Improvement of Malting Quality via MAS

Abstract: China has a large barley germplasm collection which has not been well characterized and is therefore underutilized. The Bmy1 locus encoding the β-amylase enzyme on chromosome 4H has been well characterized in the worldwide barley germplasm collections due to its importance in the malting and brewing industry. The Bmy1 locus was chosen as an indicator to understand genetic potential for improvement of malting quality in Chinese landraces and Tibetan wild barley. The genetic diversity of 91 barley accessions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Total β-amylase activity did not change over time, consistent with its synthesis during grain development. Free β-amylase activity increased during germination and varied between genotypes, consistent with the release of bound β-amylase and previous reports 16 , 19 , 61 63 . Notably, genotype-specific differences in free β-amylase activity at grain maturity correlated with aleurone area, proportion and width.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Total β-amylase activity did not change over time, consistent with its synthesis during grain development. Free β-amylase activity increased during germination and varied between genotypes, consistent with the release of bound β-amylase and previous reports 16 , 19 , 61 63 . Notably, genotype-specific differences in free β-amylase activity at grain maturity correlated with aleurone area, proportion and width.…”
Section: Discussionsupporting
confidence: 91%
“…Enzymes involved in starch hydrolysis include α-amylase, which hydrolyses α-1,4-glycosidic bonds of starch polysaccharides and β-amylase, which is synthesised during grain development, and during germination acts to liberate the disaccharide maltose from the non-reducing end of starch molecules 16 , 56 – 58 . Function of these enzymes is critical for germination 59 , 60 , and previous studies show that mature grain β-amylase content varies between barley genotypes 61 63 .…”
Section: Discussionmentioning
confidence: 98%
“…Development of tightly linked molecular markers to underlying candidate genes and identification of desirable alleles is necessary for effective MAS. Diagnostic molecular markers have been identified for numerous traits such as waterlogging tolerance (Zhang et al 2016); malting quality (Gong et al 2013;Xu et al 2018b) and disease resistance (Dinglasan et al 2019;Zantinge et al 2019). Despite numerous studies having mapped significant QTL associated with grain size characteristics on all seven barley chromosomes, limited research fine mapping these regions has impacted the development of diagnostic molecular markers for breeding purposes.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Haruna Nijo has a high thermostability of β-amylase, 7 and it also shows different Bmy1 allele for β-amylase activity from Morex. 8 It is also shown that Haruna Nijo has a high malt extract (related to beer production) by QTL analysis. 9 To enhance the utility of Haruna Nijo for breeding, a suite of genomics resources were developed including: an EST collection, transcript map construction, 10 , 11 a BAC library, 12 454-based WGS sequencing 3 and full-length (FL) cDNA sequencing and analysis 13 , 14 (available at , 7 November 2015, date accessed, with functions of expression profiling and genome browsing).…”
Section: Introductionmentioning
confidence: 97%